2004
DOI: 10.1093/brain/awh172
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the brain regions crucial for orchestrating speech articulation

Abstract: A traditional method of localizing brain functions has been to identify shared areas of brain damage in individuals who have a particular deficit. The rationale of this 'lesion overlap' approach is straightforward: if the individuals can no longer perform the function, the area of brain damaged in most of these individuals must have been responsible for that function. However, the reciprocal association, i.e. the probability of the lesion causing the deficit, is often not evaluated. In this study, we illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
236
8
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(280 citation statements)
references
References 35 publications
27
236
8
7
Order By: Relevance
“…Wise et al, 1999;Bohland and Guenther, 2006;Ozdemir et al, 2006;Soros et al, 2006). These findings appear to conflict with the large body of lesion data that supports the traditional view of left hemisphere dominance of speech production (Duffy, 1995;Dronkers, 1996;Kent and Tjaden, 1997;Hillis et al, 2004). The present results reconcile these findings: while both hemispheres contribute to speech production, feedforward control is predominantly subserved by the left hemisphere whereas auditory feedback control is subserved by right hemisphere frontal regions.…”
Section: Implications For Speech Disorderscontrasting
confidence: 80%
“…Wise et al, 1999;Bohland and Guenther, 2006;Ozdemir et al, 2006;Soros et al, 2006). These findings appear to conflict with the large body of lesion data that supports the traditional view of left hemisphere dominance of speech production (Duffy, 1995;Dronkers, 1996;Kent and Tjaden, 1997;Hillis et al, 2004). The present results reconcile these findings: while both hemispheres contribute to speech production, feedforward control is predominantly subserved by the left hemisphere whereas auditory feedback control is subserved by right hemisphere frontal regions.…”
Section: Implications For Speech Disorderscontrasting
confidence: 80%
“…Recent lesion studies (Dronkers, 1996;Bates et al, 2003;Dronkers, Ogar, Willock, and Wilkins, 2004) as well as functional neuroimaging studies (Wise et al, 1999;Ackermann andRiecker, 2004,Shuster andLemieux, 2005) have identified the anterior insula as a critical area subserving articulatory planning or implementation of speech. However, Hillis et al (2004) using diffusion-weighted and perfusion-weighted imaging found no association between apraxia of speech and the left insula but strongly implicated Broca's area in apraxia of speech. The results of the current study do suggest that the insula plays an important role in the coordination of articulatory movements.…”
Section: Neural Substrates Of the Deficitmentioning
confidence: 88%
“…Previous studies implicate anterior brain structures including Broca's area, the pre-motor and motor regions for face and mouth areas, the white matter deep to these structures, the basal ganglia, and the insula (Hillis et al, 2004;Damasio, 1998;Cummings, 1993;Naeser et al, 1989). Moreover, Naeser et al showed increased severity of speech deficit when two neuroanatomical areas were affected by lesion: (1) the most medial and rostral portion of the subcallosal fasciculus (deep to Broca's area) and (2) the periventricular white matter near the body of the lateral ventricle deep to the lower motor/ sensory cortex for mouth (affecting motor execution and feedback).…”
Section: Neural Substrates Of the Deficitmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, since the insula is in the core of the middle cerebral artery territory, insular damage commonly correlates with damage in adjacent locations, and the damage may be co-attributed to the insula by these methods (Hillis et al, 2004).…”
mentioning
confidence: 99%